SUPERIOR SPORTS SURVEY IN SRAGEN - SAMIJO, S. (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2019)
Sport has an important meaning in an effort to improve the quality of human resources and sports cannot be separated from human life. Because human life consists of two aspects, namely physical and spiritual aspects that cannot be separated. If both aspects develop and grow in harmony, there will be a harmonious life in its growth. The harmony of physical and spiritual life in humans could be achieved among others by exercising. Many things are implanted with sports activities. According to Law No. 3 of 2005 that: "National Sport aims to maintain and improve health and fitness, achievement, quality instill moral values of sportsmanship, discipline, strengthen the brotherhood of the nation, strengthen national defense, Indonesia’s sports achievements slump lately partly because the weakness of the systems of coaching which includes breeding problems, and increase achievement. Sporting achievement can be achieved if the problems and regeneration are done. The improvement of achievement effort is not only done by Indonesia alone. Almost all countries are doing the same thing, trying to show training superiority in international achievement. For example, Thailand to break through two major programs of Asia, in the Philippines with the program "Gintong Allay" and of course Indonesia with the program "Golden Garuda" are sought to be four Asia in 2002. The fact is indicated that sports coaching is essential to achieve a high achievement, which in turn can be the name of nation and state in the international arena.